Quinolines: the role of substitution site in antileishmanial activity - Elso, Orlando G.; García Liñares, Guadalupe (Frontiers in Chemistry, 2025)
Leishmaniasis is one of the most widespread parasitic diseases in the world, primarily affecting the poorest and most vulnerable populations. The development of new therapeutic agents that are more efficient, safe, and selective remains a challenge. The quinoline framework emerges as a privileged scaffold for this purpose. This mini-review comprehensively analyses advancements from the last two decades on 2-, 3-, 6-, and 8-substituted quinolines, as well as polysubstituted analogues, as potential antileishmanial agents, focusing on how the position and nature of substituents influence their activity. Although the assays were conducted in different Leishmania species, 2- and 6-substituted quinolones generally show greater activity, often enhanced by the presence of halogen or hydroxyl groups.